DNA DAMAGE BINDING PROTEIN2 Shapes the DNA Methylation Landscape. Issue 9 (16th August 2016) - Schalk, Catherine; Drevensek, Stéphanie; Kramdi, Amira; Kassam, Mohamed; Ahmed, Ikhlak; Cognat, Valérie; Graindorge, Stéfanie; Bergdoll, Marc; Baumberger, Nicolas; Heintz, Dimitri; Bowler, Chris; Genschik, Pascal; et al.
Abstract : DDB2 influences de novo DNA methylation by interacting with ARGONAUTE4 and controlling the local abundance of 24-nucleotide short interfering RNAs. Abstract: In eukaryotes, DNA repair pathways help to maintain genome integrity and epigenomic patterns. However, the factors at the nexus of DNA repair and chromatin modification/remodeling remain poorly characterized. Here, we uncover a previously unrecognized interplay between the DNA repair factor DNA DAMAGE BINDING PROTEIN2 (DDB2) and the DNA methylation machinery in Arabidopsis thaliana . Loss-of-function mutation in DDB2 leads to genome-wide DNA methylation alterations. Genetic and biochemical evidence indicate that at many repeat loci, DDB2 influences de novo DNA methylation by interacting with ARGONAUTE4 and by controlling the local abundance of 24-nucleotide short interfering RNAs (siRNAs). We also show that DDB2 regulates active DNA demethylation mediated by REPRESSOR OF SILENCING1 and DEMETER LIKE3. Together, these findings reveal a role for the DNA repair factor DDB2 in shaping the Arabidopsis DNA methylation landscape in the absence of applied genotoxic stress.